Gastric Perforation Associated with Candidiasis and NSAIDS - Aquaresta, Febriana; Kawilarang, Arthur Pohan; Endraswari, Pepy Dwi (Indonesian Journal of Tropical and Infectious Disease, 2020)
Invasive candidiasis is an important health-care-associated fungal infection. Candida is often described as an opportunistic pathogen. It is commensal flora in the gastrointestinal tract. Invasive candidiasis can happen usually because of a consequence of increased or abnormal colonization together with a local or generalized defect in host defenses. Candidiasis can occur in patients with HIV, therapy with a broad-spectrum antibiotic, transplant organ, and immunocompromised. Most cases of gastric perforation occur as complications of Peptic Ulcer Disease (PUD), Nonsteroidal Anti-Inflammatory Drugs (NSAIDs) and gastric neoplasms, but candidiasis as a cause of gastric perforation is very rare. This study aims to reveal the correlation between gastric perforation with candidiasis and NSAIDs. It was reported that a 57-year-old East Java Indonesian female presented with severe epigastric pain, generalized peritonitis, fever, nausea also vomiting and had a history of NSAIDs used for five years. The patient was taken to the general surgery of Dr. Sutomo Surabaya Hospital and performed exploratory laparotomy. A gastric perforation was discovered in the antrum. Microbiology culture examination from biopsy gastric tissue revealed an intense fungal growth from sabouraudagar medium and there is no other microorganism that grew in aerobic culture. Candida albicans was identified by VITEK® 2 COMPACT. Histopathological examination from biopsy gastric tissue was performed by Olympus CX-21 microscope, showed invasive Candida albicans consisting of numerous fungal yeasts and pseudohyphae invading and destroying the gastric wall. The patient was subsequently treated with fluconazole anti-fungal and discharge home after nine days postoperative period in good condition. From this result, we suggest using an antifungal treatment for patients who use NSAIDs for long periods to prevent candidiasis.